Struktur Nafkah Rumahtangga Petani Transmigran : Studi Sosio-Ekonomi di Tiga Kampung di Distrik Masni Kabupaten Manokwari - P. Tulak, Paulina; Hadi Dharmawan, Arya (Sodality: Jurnal Sosiologi Pedesaan, 2009)
Among the primary objectives of transmigration program are to increase the economic status of transmigrant farm-households and enhancing rural infrastructures of the local region. To see wether such objective is attainable, a study of transmigrant farm households has been conducted in West Papua. The study attempts: (1) to know whether there is any relation between the socio-cultural/ethnical background of the transmigrant farm-household with the achievement of welfare status, (2) to analyze factors influencing to the income level of transmigrant farm-households, and (3) to understand how the farm households enhance the degree of economic status by building numerous livelihood strategies. The methods as used in the analysis are: (1) income level analysis of the households, (2) gini-ratio analysis, and (3) descriptive analysis. The results of this study are: socio-cultural (ethnical) setting of transmigrant has a substantial influence to the achievement of welfare level. Javanese transmigrant showed a much higher income achievement due to their strong engagement in the non-farm economy, as compared to Papuanese transmigrant farm-households. The non-farm economy provides a strong basis for economic growth at household level. However, the growth of non-farm economy unexpectedly caused an increasing tendency of income disparity among different farm household strata. Since non-farm economy shares a positive contribution for regional economic growth, the study concludes, that the government needs to take seriously this economic sector into account when regional development needs to be well-accomplished in West Papua.